Auriculotherapy in prevention of migraine attacks: an open randomized trial - Michel-Cherqui, Mireille; Ma, Sabrina; d’Ussel, Marguerite; Ebbo, David; Spassova, Antoinette; Chaix-Couturier, Carine; Szekely, Barbara; Fischler, Marc; Lemaire, Nicolas; Le Guen, Morgan (Frontiers in Neurology, 2023)
Use of auriculotherapy to prevent episodic migraine pain has seldom been reported. The aim of this open study was to show that three sessions of auriculotherapy, 1 month apart, using semi-permanent needles decrease frequency and intensity of an attack in patients presenting episodic migraine. A total of 90 patients were randomized to the treatment group (AUR group, n = 58) or the control group (C group, n = 32). Four patients dropped out during the study (three in the AUR group and one in the C group). The number of days with migraine and non-migraine headache was similar when the analysis focused on the 3 months of the study or on the difference in each group of this number between the 3 months preceding the inclusion and the 3 months of the study (p = 0.123). AUR group patients had fewer days with non-migraine headache (p = 0.011) and took less Triptans (p = 0.045) than group C. Number of days with migraine, sum of the pain intensities of all migraines and non-migraine headaches, and total number of analgesics taken, other than triptan, were similar between groups. MIDAS score decreased with time in the AUR group while it increased in the C group whether in absolute values (p = 0.035) or as categories (p = 0.037). These contrasted results should lead to further study of the effectiveness of auriculotherapy for the prevention of migraine. Clinical trail registration: Protocol registered on the Clinicaltrials.gov, website (January 30, 2017, NCT03036761).